2006
DOI: 10.1556/avet.54.2006.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mouse embryos after vitrification depending on the cooling rate of the cryoprotectant solution

Abstract: The aim of the study was to determine the relationship between the rate of cooling of eight-cell mouse embryos to the temperature of liquid nitrogen (-196 °C) and their developmental capacity after thawing on the basis of their ability to leave the zona pellucida ('hatching') during in vitro culturing. Eight-cell embryos were obtained from superovulated female mice and divided into three experimental and one control group. Embryos from the experimental groups were cryopreserved by the vitrification method us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In previous studies, cryopreservation of single-cell embryos up to the blastocyst stage showed that embryos at the morula stage tolerated the conditions of vitrification. In contrast, two-cell and blastocyst embryos were unable to tolerate the freezing conditions [27,28]. Van der Auwera et al [27] showed that the concentration and duration of the cryopreservation solution, cell size, membrane permeability, and the stage of embryonic development are important factors that influence the success of vitrification.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, cryopreservation of single-cell embryos up to the blastocyst stage showed that embryos at the morula stage tolerated the conditions of vitrification. In contrast, two-cell and blastocyst embryos were unable to tolerate the freezing conditions [27,28]. Van der Auwera et al [27] showed that the concentration and duration of the cryopreservation solution, cell size, membrane permeability, and the stage of embryonic development are important factors that influence the success of vitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Hredzák et al . (2006) observed a decrease in hatching rate of blastocysts produced from 8-cell mouse embryos vitrified in straws (8%) compared to the group frozen in pipetting tips (38%) or introduced dropwise directly into liquid nitrogen (60%). An important role of cooling rates of the solution is ascribed to the freezing container, thermal conductivity of its walls and the volume of vitrification solution (Liebermann et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For human embryos vitrification has been shown to be more favourable than slow freezing with regard to survival, ongoing pregnancy and implantation rates (Kuleshova & Lopata, 2002; Stehlik et al ., 2005). The survival rate after vitrification differs depending on the method of cryopreservation (Zhao et al ., 2007), number of steps, cooling rates (Hredzák et al ., 2006), type and concentration of cryoprotective agent (CPA) (Zhou et al ., 2007), developmental stage of embryo (Zhou et al ., 2005) as well as the embryo quality alone (Fabian et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is inexpensive and easy to assemble. Similar methods of vitrifying embryos in a droplet have been reported previously (20,21), wherein a droplet of vitrification solution containing embryos is cooled by direct dipping into LN 2 . With this method, we frequently encountered problems of retrograde filling of the droplet into the pipet tip, due to the contraction of air volume within the pipet tip when the sample is lowered but before reaching the LN 2 surface.…”
mentioning
confidence: 89%